Pengaruh Konsentrasi dan Lama Perendaman Air Kelapa terhadap Pertumbuhan Stek Tanaman Tomat (Solanum Lycopersicum) - Khabibatuz zakiyah (Universitas Tidar, 2025)
Tomato (Solanum lycopersicum) is a fruit vegetable that is widely cultivated in Indonesia. Currently tomato plants are propagated generatively using seeds and are constrained by disease attacks, especially viruses, namely Tomato Yellow Leaf Curl Virus (TYLCV), so it is necessary to improve cultivation using the cutting method. The growth of shoots and root cuttings can be enhanced by using coconut water. The aim of this research is to determine the effect of concentration and soaking time in coconut water on the growth of tomato plant cuttings. The research was canducted from June 1st to July 14th 2022 at Bojong Hamlet, Maduretno Village, Kaliangkrik District, Magelang Regency with latosol soil type and altitude 763 meters above sea level. The research used polybags with a factorial experiment (4x3) arranged in a Randomized Completely Block Design (RCBD) with two treatment factors and repeated three times as blocks. The first factor is the concentration of coconut water 25, 50, 75 and 100%. The second factor is the soaking time of coconut water 4, 8 and 12 hours. The results showed that the concentration of 25% coconut water gave the highest growth on fresh weight of shoot, dry weight of shoot, number of roots, fresh weight of roots and dry weight of roots and number of shoots at a concentration of 49,04%. Soaking time of 10,73 hours in coconut water resulted the highest on dry weight of top stover on cuttings of tomato plants. Concentration of 100% coconut water and soaking time of 12 hours of coconut water produced the highest on fresh weight of shoot and dry weight of shoot on cuttings of tomato plants.